Analisis Reaksi Pasar Modal Terhadap Pengumuman Integrasi BUMN ke Dalam Danantara: Studi Kasus Saham BUMN Serta Afiliasi BUMN Terbuka dan Indeks Harga Saham Gabungan (IHSG) - Sumasaputra, Hendry Pramudipta; Rohman, Abdul; Milwan, Milwan (Jayapangus Press, 2025)
This study examines the Indonesian capital market's response to the announcement of the integration of State-Owned Enterprises (BUMN) into Danantara, a new Sovereign Wealth Fund (SWF). Given BUMNs' strategic economic role, this February 24, 2025 announcement was a market event with significant implications. The primary objective was to evaluate the presence of significant abnormal returns on 25 BUMN/affiliate shares and the Jakarta Composite Index (IHSG), compare returns, and examine absolute share price changes. Adopting a quantitative event study methodology, the research used secondary data from the Indonesia Stock Exchange (BEI), including daily closing prices for the specified shares and the IHSG. The data was collected during an event window from five days before to five days after the announcement. Analysis was conducted using the Market Adjusted Model, with hypotheses tested via a one-sample t-test and a paired-samples mean difference test (Wilcoxon Signed Ranks Test) at a 0.05 significance level. The results show no statistically significant abnormal returns on either BUMN/affiliate shares or the IHSG. However, there was a significant decrease in the average price of both asset groups following the announcement. This finding supports the semi-strong form of the Efficient Market Hypothesis (EMH), as public information was integrated efficiently, preventing persistent abnormal gains. The significant price drop reflects pessimistic and cautious investor sentiment, indicating concerns over the complexity of this restructuring. The homogeneous and systemic market reaction suggests the policy is viewed as a large-scale transformation with potentially significant consequences.